Upregulation of TNF-α and IL-6 mRNA in mouse liver induced by bacilli Calmette-Guerin plus lipopolysaccharide - Liu Dao-fang; Wei Wei; Song Li-hua (Acta Pharmacologica Sinica; Vol 27, No 4 (April 2006): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the mechanism of immunological liver injury induced by bacilli Calmette-Guerin (BCG) plus lipopolysaccharide (LPS). Methods: Mice were injected via the tail vein with 125 mg/kg BCG, and 12 d later, the mice were injected intravenously with different doses of LPS (125, 250, or 375 μg/kg). Serum alanine aminotransferase (ALT) activity and liver pathological changes were examined. The expression of tumor necrosis factor (TNF)-α, interleukin (IL)-6, lipopolysaccharide binding protein (LBP) and CD14 mRNA, and NF-κB and IκB-α protein in mouse liver at different time points after BCG and LPS injection were measured using RT-PCR, immunohistochemistry and Western blotting analysis, respectively. Results: The activity of serum ALT in mice treated with BCG and LPS was significantly increased. Different degrees of liver injury, such as inflammatory cell infiltration, spotty necrosis, piecemeal necrosis, even bridging necrosis, could be seen in liver sections from mice after BCG and LPS administration. Furthermore, the levels of TNF-α and IL-6 mRNA in mouse liver were significantly elevated after administration of BCG plus LPS (P